Geochemistry of Sebangau swamp forest (SEB 1B) peat core from Borneo - Dan J Charman; Angela V Gallego-Sala (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.